Impact of sample acidification and extract storage on hormone receptor-mediated and oxidative stress activities in wastewater - Maria Yu; Geeta Mandava; Elin Lavonen; Agneta Oskarsson; Johan Lundqvist (IWA Publishing, 2024)
An underemphasized aspect of sampling strategies in effect-based in vitro testing is to determine suitable collection and preparation techniques. In the current study, the impact of sample acidification on bioactivities was assessed using in vitro bioassays for hormone receptor-mediated effects (estrogen receptor [ER] and androgen receptor [AR]) and the oxidative stress response (Nrf2 activity). Sampling was conducted at a recently upgraded Swedish wastewater treatment plant. Future plans for the treated wastewater include reuse for irrigation or as a potential drinking water source. In the AR and Nrf2 assays, acidification decreased bioactivities in the wastewater influent sample extracts, whereas acidification increased bioactivities following further treatment (disc filtration). In the ER assay, acidification had no impact on the observed bioactivities in the sample extracts. A secondary objective of the study was to assess the stability of the sample extracts over time. Lower activities were detected in the ER and AR assays in all extracts after storage for approximately 1 year. Nrf2 activities did not decrease over time, but rather increased in some of the acidified sample extracts. Overall, the findings suggest that sampling strategies involving acidification may need to be tailored depending on the selected bioassay(s) and the type of wastewater treatments being assessed. HIGHLIGHTS Sample acidification impacted in vitro bioactivities of wastewater extracts.; Impact of acidification differed before versus after disc filtration treatment.; Storage time of approximately 1 year reduced hormone receptor-mediated bioactivities.; Findings suggest against a 'one-size-fits-all' approach involving sample acidification and storage.;